(untitled) (Global Journal of Human-Social Science, 2023)
This mapping covers almost 6 thousand trans cover texts published in Folha de S Paulo between 1960 and 2017 and is part of the understanding of the media as a fundamental agent in the sphere of representations directly influencing the dynamics of contemporary societies The reflection on the discourse and narratives conveyed in this periodical in which transvestites and transsexuals gradually migrate from associations to arts and shows 23 19 of occurrences becoming associated with marginality and criminality 36 88 of the total in the fait divers reveals the discursive flow of the citations towards the ads of prostitution a fact that invites us to go through this historical narrative to problematize how such contents are configured today